EKSEPSI PLURIUM LITIS CONSORTIUM (Studi Terhadap Putusan Pengadilan Tinggi Semarang No. 401/Pdt/2002/PT. Smg jo. Putusan Pengadilan Negeri Purwokerto No.41/Pdt.G/2000/PN.Pwt) - Muflichah, Siti; Subekti, Trusto; Faradz, Haedah (Jurnal Dinamika Hukum, 2008)
In the civil jurisdiction, truth searched is the formal truth. This matter of course different from the criminal justice, where truth searched is material truth. Searching the formal truth, meaning that judge may not be abysmal of boundary that raised by the parties. This matter contain the congeniality, that verification process is  not see at wight or content, but to wide of case scope or dispute that raised by the parties. In this case judge have the passive character. in civil jurisdiction, truth searched  is a truth that relying on  formal verification. The Judge decision shall contain the rule of law element, justice and benefit. For the reason judge have to  careful, goodness in making draft of decision and also decision intake later. In Case No. 401/ Pdt / 2002 / PT. Smg, The Judge of High Court  of middle of Java made the decision by strengthening decision of District Court of Purwokerto in case  No. 41/Pdt.G/2000/PN Pwt. This Judge Decision represent an example of careless of the judge in make decision. exception of the lack of party had refused. Therefore, judge have to consider this matter in its decision. Therefore, judge have to consider this matter in its decision. This matter of course relative harm the plaintiff, because if suing is not accepted, plaintiff can improve/ repair its suing or make a lawsuit to the court newly again. But refusedly of suing make the plaintiff cannot improve/ repair its suing or make the new suing again. finally, the decision which is not careful will not fulfill the rule of law elements, justice and benefit. Kata kunci: kebenaran formil, penggugat, tergugat, turut tergugat, syarat formil gugatan